Patterns of urinary tract infections (UTIS) in a South African Public Hospital - Jaji, Benhilda (My University, 2021)
Introduction: Urinary tract infections (UTIs) are amongst the most common types of bacterial infection in public hospitals and the second most common reason for empirical antibiotic treatment. Optimal treatment could decrease morbidity and mortality in women, also battling the ongoing crises of increasing antibiotic resistance. The aim of this study was to determine antimicrobial resistance patterns of UTIs in the study hospital, in order to recommend an effective treatment protocol and infection management practices. Method: This study was conducted on 200 urine samples collected from outpatient departments of the study hospital. The antimicrobial susceptibility patterns of isolated bacteria were determined by disk diffusion method (Kirby–Bauer). Bacterial isolates were identified using the MicroScan. Results: A total of 238 bacterial isolates were found in uncomplicated UTIs. Among them, the most predominant bacteria were Escherichia coli (43.6%). A total of 194 bacterial isolates were found in complicated UTIs, where similarly E. coli (31.2%) was the most predominant bacteria encountered. Antibiotic susceptibility patterns showed that almost all of the isolates were resistant to at least one antibiotic. Highest resistance percentage of the isolates in uncomplicated UTIs was observed in cephalexin (96.2%) followed by co-trimoxazole (91.3%). Highest resistance percentage of the isolates in complicated UTIs was observed in cephalexin and co trimoxazole (100%). Conclusion: This study provides evidence for an updated treatment protocol, hence, providing valuable tools for antimicrobial stewardship in South Africa. Knowing the resistance levels is key to effective and cost-effective empirical prescribing. Co trimoxazole resistance rates are 100%, in which case a single 3 g dose of fosfomycin is likely to be the most cost-effective treatment option
A dissertation submitted in fulfilment of the requirements for the degree of Master of Pharmacy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021